Medial Sesamoidectomy as a Local Autograft Source in Revision or Complex First Metatarsophalangeal Joint Arthrodesis - Aaron Tran MD; Brennan Enright MD; Rachel Reichenbach BS; Jordan Henderson BS; David Jaffe MD (Foot & Ankle Orthopaedics, 2025)
Background: Arthrodesis of the first metatarsophalangeal (MTP) joint is a well-established procedure with excellent outcomes for patients with forefoot disorders. Routine bone grafting is not typically required, but bone graft may be necessary in the setting of revision surgery. Because of potential harvesting morbidity and time associated with an extra incision, allograft bone is frequently used. In this study, we describe the outcomes of an approach to first MTP fusion with simultaneous medial sesamoidectomy for utilization as autograft. Methods: A retrospective review of all first MTP arthrodesis cases performed by one fellowship-trained foot and ankle surgeon were identified. Operative reports and radiographs were reviewed identifying patients who underwent simultaneous medial sesamoidectomy for autograft purposes. Indications for sesamoidectomy harvesting were noted. The primary outcome reviewed was fusion rate. Overall nonunion rates and patient outcomes were collected and compared between those undergoing sesamoidectomy for grafting and those undergoing standard procedure arthrodesis. Results: A total of 107 patients underwent first MTP arthrodesis. Of these, 24 underwent concurrent sesamoidectomy grafting with 9 requiring additional calcaneal grafting. Indications for the sesamoidectomy group included 5 primary cases of erosive hallux rigidus, 2 cases of hallux valgus, 6 nonunions, 3 failed Cartiva implants, 2 cases of avascular necrosis, 4 failed arthroplasties, and 2 conversion bunionectomy. All 24 patients in the sesamoidectomy group achieved successful union. For context, the broader cohort undergoing first MTP arthrodesis had a fusion rate of 92.1%. All patients in the sesamoidectomy group were satisfied with their surgical outcome. Conclusion: This study found highly successful fusion rates in a potentially higher risk population with the use of local autografting from the medial sesamoid. The medial sesamoid serves as a freely available, structurally supportive graft material for first MTP arthrodesis that can be readily harvested via the same incision, potentially reducing the need for additional graft sites. However, given the retrospective nature, single-surgeon cohort, and small sample size, further studies are warranted to confirm these findings and evaluate comparative outcomes. Level of Evidence: Level III, retrospective comparative study.